What is a gospel? - Watson, Francis 1956- (Grand Rapids, Michigan William B. Eerdmans Publishing Company, 2022)
Machine generated contents note: Table of Contents1. What Is a Gospel? -- 2. Seven Ways to Dispose of Judas Iscariot -- 3. How Did Mark Survive? -- 4. Does Luke Need Q? -- 5. Q and the Logia: On the Discovery and Marginalizing of P.Oxy.1 -- 6. Luke Rewriting and Rewritten -- 7. The Gospel of the Apostles: The Epistula Apostolorum and the Johannine Tradition -- 8. Jesus versus the Lawgiver: Narratives of Apostasy and Conversion -- 9. Making Sense of the Betrayer: The Gospel of Judas and Its Predecessors -- 10. Reception as Corruption: Tertullian and Marcion in Quest of the True Gospel -- 11. Toward a Redaction-Critical Reading of the Diatessaron Gospel -- 12. Lindisfarne and the Gospels: The Art of Interpretation -- 13. Eschatology and the Twentieth Century: On the Reception of Schweitzer in English -- 14. A Reply to My Critics.
"A collection of essays, new and old, from noted biblical scholar Francis Watson on viewing early gospel literature as a unified genre that transcends conventional categories of canonical, noncanonical, and heretical"--
"When Christians speak of "the gospels" they're usually referring to Matthew, Mark, Luke, and John. Other ancient writings about the life of Jesus are generally considered noncanonical or heretical. But what if these other gospel writings-including the Gospel of Thomas, the Gospel of Judas, and the Protevangelium of James-aren't fundamentally different from the four canonical gospels? In this follow-up to Gospel Writing: A Canonical Perspective, noted biblical scholar Francis Watson makes the case that viewing early gospel literature as a unified genre-sharing significant similarities in sources, content, and goals-allows us to discern important interrelated aspects that are lost amid the usual categories. Watson's critical approach enables modern readers of the Bible to break free of fraught scholarly assumptions in order to better understand early Christian identity formation and beliefs"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Jesus Christ; Bible -- Criticism, interpretation, etc; Christian literature, Early -- History and criticism; Apocryphal books (New Testament) -- Criticism, interpretation, etc; RELIGION / Biblical Commentary / New Testament / Jesus, the Gospels & Acts; RELIGION / Biblical Studies / New Testament / General